Crossover and rechallenge with pembrolizumab in recurrent patients from the EORTC 1325-MG/Keynote-054 phase III trial, pembrolizumab versus placebo after complete resection of high-risk stage III melanoma. (November 2021) - Eggermont, Alexander MM.; Meshcheryakov, Andrey; Atkinson, Victoria; Blank, Christian U.; Mandala, Mario; Long, Georgina V.; Barrow, Catherine; Di Giacomo, Anna Maria; Fisher, Rosalie; Sandhu, Shahneen; Kudchadkar, Ragini; Ortiz Romero, Pablo Luis; et al.
Abstract: Background: In the phase III double-blind European Organisation for Research and Treatment of Cancer 1325/KEYNOTE-054 trial, pembrolizumab improved recurrence-free and distant metastasis-free survival in patients with stage III cutaneous melanoma with complete resection of lymph nodes. In the pembrolizumab group, the incidence of grade I–V and of grade III–V immune-related adverse events (irAEs) was 37% and 7%, respectively. Methods: Patients were randomised to receive intravenous (i.v.) pembrolizumab 200 mg (N = 514) or placebo (N = 505) every 3 weeks, up to 1 year. On recurrence, patients could enter part 2 of the study: pembrolizumab 200 mg i.v. every 3 weeks up to 2 years, for crossover (those who received placebo) or rechallenge (those who had recurrence ≥6 months after completing 1-year adjuvant pembrolizumab therapy). For these patients, we present the safety profile and efficacy outcomes. Results: At the clinical cut-off (16-Oct-2020), in the placebo group, 298 patients had a disease recurrence, in which 155 (52%) crossed over ('crossover'). In the pembrolizumab group, 297 patients completed the 1-year treatment period; 47 had a recurrence ≥6 months later, in which 20 (43%) entered the rechallenge part 2 ('rechallenge'). In the crossover group, the median progression-free survival (PFS) was 8.5 months (95% confidence interval [CI] 5.7–15.2) and the 3-year PFS rate was 32% (95% CI 25–40%). Among 80 patients with stage IV evaluable disease, 31 (39%) had an objective response: 14 (18%) patients with complete response (CR) and 17 (21%) patients with partial response. The 2-year PFS rate from response was 69% (95% CI 48–83%). In the rechallenge group, the median PFS was 4.1 months (95% CI 2.6–NE). Among 9 patients with stage IV evaluable disease, 1 had an objective response (CR). Among the 175 patients, 51 (29%) had a grade I–IV irAE and 11 (6%) had a grade III–IV irAE. Conclusions: Pembrolizumab treatment after crossover yielded an overall 3-year PFS rate of 32% and a 39% ORR in evaluable patients, but the efficacy (11% ORR) was lower in those rechallenged. Highlights: Adjuvant therapy with pembrolizumab prolongs RFS and DMFS in stage III melanoma. The EORTC 1325/KEYNOTE-054 adjuvant therapy trial has a formal crossover design. Efficacy of pembrolizumab in relapsed placebo-treated patients was as expected. Efficacy of pembrolizumab in relapsed pembrolizumab-treated patients was lower.